Developing a Conceptual Partner Matching Framework for Digital Green Innovation of Agricultural High-End Equipment Manufacturing System Toward Agriculture 5.0: A Novel Niche Field Model Combined With Fuzzy VIKOR - Yin, Shi; Wang, Yuexia; Xu, Junfeng (Frontiers in Psychology, 2022)
Digital green innovation (DGI) is the core factor that affects the digitalization and decarbonization strategy of agricultural high-end equipment manufacturing (AHEM) system. However, although AHEM enterprises actively cooperate with academic research institutes to develop agricultural high-end equipment, there are many obstacles in the process of DGI. Moreover, the integration of digital technology and green innovation from the perspective of partner matching for AHEM system has not been fully introduced into current literatures. Hence, this study aimed to i) establish a suitable framework system for AHEM system in general, ii) quantify the academic research institutions selection of DGI based on niche theory, and iii) propose an extended niche field model combined with fuzzy VIKOR model. Firstly, a theoretical framework consisting of three core elements of technology superposition, mutual benefit and mutual trust and technological complementarity was constructed based on niche intensity and niche overlap degree. DGI ability superposition of technology, mutual trust and technical complementarity are beneficial for transferring DGI knowledge from academic research institutes to the AHEM industry. Secondly, triangle fuzzy number and prospect theory combined with VIKOR method were introduced into the field theory to construct the complementary field model of DGI resources. The niche field model has been successfully applied to practical cases to illustrate how the model can be implemented to solve the problem of DGI partner selection. Thirdly, the results of a case study shows that the criteria framework and the niche field model can be applied to real-world partner selection for AHEM enterprises. This study not only puts forward the standard framework of niche fitness evaluation based on niche theory, but also establishes the niche domain model of innovation partner selection management based on niche theory. The standard framework and novel niche field model can help enterprises to carry out digital green innovation in the development of high-end agricultural equipment. The study has theoretical and practical implications. i) constructing a criteria framework based on niche theory; ii) developing a novel niche field model for DGI partner selection of AHEM enterprises; iii) assisting an AHEM enterprises to perform DGI practice.